ANALISIS FILSAFAT ILMU DALAM KONTEKS KOMUNIKASI PEMBANGUNAN - Zamroatul Fuaddah (IAIN SYEKH NUR JATI, 2023)
Philosophy has an important role in the development of communication science, especially development communication which shapes the practices and social realities of society. A thorough understanding of the philosophy of scientific concepts, such as axiology, epistemology, and ontology, is the key to guiding development communication more meaningfully and effectively in supporting social progress and improving community welfare. The method used in this research is a literature review study, where researchers collect data from indexed books and journals. The researcher attempts to explain how philosophical studies have been carried out in development communication over the last ten years. The results of this research will provide a better understanding of the role of philosophy of science in the context of developmental communication and how axiology, epistemology and ontology influence developmental information communication practices. These findings will contribute to a better understanding of how development communication can be more effective, ethical and sustainable to support social, economic, political and cultural development goals.